Documentary across platforms : reverse engineering media, place, and politics - Zimmermann, Patricia Rodden (Indiana University Press, 2019)
"In Documentary Across Platforms, noted scholar of film and experimental media Patricia R. Zimmermann offers a glimpse into the ever-evolving constellation of practices known as "documentary" and the way in which they investigate, engage with, and interrogate the world. Collected here for the first time are her celebrated essays and speculations about documentary, experimental, and new media published outside of traditional scholarly venues. These essays envision documentary as a complex ecology composed of different technologies, sets of practices, and specific relationships to communities, engagement, politics, and social struggles. Through the lens of reverse engineering--the concept that ideas just like objects can be disassembled to learn how they work and then rebuilt into something new and better--Zimmermann explores how numerous small-scale documentary works present strategies of intervention into existing power structures. Adaptive to their context, modular, and unfixed, the documentary practices she explores exploit both sophisticated high-end professional and consumer-grade amateur technologies, moving through different political terrains, different platforms, and different exhibition contexts. Together these essays demonstrate documentary's role as a conceptual practice to think through how the world is organized and to imagine ways that it might be reorganized with actions, communities, and ideas"--